Coupled interactions of the monsoons - Vasubandhu Misra (Geophysical Research Letters)
A case is made to show that all continental summer monsoon regions of the globe are manifestations of strong, coupled ocean‐land‐atmosphere interactions. It is shown from observations that the auto‐decorrelation time of the daily rainfall in the summer monsoon regions is usually in excess of 3 days. This characteristic feature of the monsoon rainfall is well simulated in a global coupled ocean‐land‐atmosphere model. The atmospheric general circulation model component integrations of the same coupled model forced with observed SST show a distinctly shorter auto‐decorrelation time of the daily monsoon precipitation. An obvious conclusion is that air‐sea coupling is essential for this feature of the monsoon rainfall to be simulated. But through additional diagnostic calculations it is also shown that the robust land‐atmosphere interactions over these regions also contribute to the lengthening of the auto‐decorrelation time of the daily continental summer monsoon rainfall.